The relationship between personality traits and sexual self-esteem and its components - Mahbobe Firoozi; Elham Azmoude; Negar Asgharipoor (Iranian Journal of Nursing and Midwifery Research, 2016)
Background: Women's sexual self-esteem is one of the most important factors that affect women's sexual satisfaction and their sexual anxiety. Various aspects of sexual life are blended with the entire personality. Determining the relationship between personality traits and self-concept aspects such as sexual self-esteem leads to better understanding of sexual behavior in people with different personality traits and helps in identifying the psychological variables affecting their sexual performance. The aim this study was to determine the relationship between personality traits and sexual self-esteem. Materials and Methods: This correlation study was performed on 127 married women who referred to selected health care centers of Mashhad in 2014–2015. Data collection tools included NEO personality inventory dimensions and Zeanah and Schwarz sexual self-esteem questionnaire. Data were analyzed through Pearson correlation coefficient test and stepwise regression model. Results: The results of Pearson correlation test showed a significant relationship between neuroticism personality dimension (r = −0.414), extroversion (r = 0.363), agreeableness (r = 0.420), and conscientiousness (r = 0.364) with sexual self-esteem (P < 0.05). The relationship between openness with sexual self-esteem was not significant (P > 0.05). In addition, based on the results of the stepwise regression model, three dimensions of agreeableness, neuroticism, and extraversion could predict 27% of the women's sexual self-esteem variance. Conclusions: The results showed a correlation between women's personality characteristics and their sexual self-esteem. Paying attention to personality characteristics may be important to identify at-risk group or the women having low sexual self-esteem in premarital and family counseling.